The Tate Gallery 1986-88 : Illustrated Biennial Report. - Tate Gallery, London (London : Tate Gallery, 1988)
Picasso, Pablo ; Wols ; Pollock, Jackson ; Braque, Georges ; Giacometti, Alberto ; Sandle, Michael ; Cragg, Tony ; Gormley, Antony ; Rothenberg, Susan ; Marden, Brice ; Houshiary, Shirazeh ; Tucker, William ; etc.
Contents: Historic British Collection Acquisitions, Modern Collection Acquisitions, Print Collection ; Exhibitions ; Education ; Publications ; ...
Engels
boek